The interaction between Mn and Fe on the precipitation of Mn/Fe dispersoids in Al-Mg-Si-Mn-Fe alloys. (15th July 2018) - Liu, C.L.; Du, Q.; Parson, N.C.; Poole, W.J.
Abstract: The formation of Mn/Fe containing precipitates during a high temperature treatment known as homogenization is important for the downstream performance of 6XXX aluminum extrusion alloys. In this work, the complex interaction between Mn and Fe during precipitation has been studied using a combination of experiments and a model that includes long range diffusion of Fe and Mn and a short range precipitation model. The results reveal the unusual phenomenon where Fe first diffuses from the constituent particles to the dispersoids, thereby increasing their volume fraction, and then at longer times reverses direction to diffuse back to the constituent particles. Graphical abstract: Unlabelled Image